2022
DOI: 10.1088/1755-1315/1024/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Family Characteristics and Anemia in Relation to Preference and Food Variety in Infant Complementary Food

Abstract: After exclusive breastfeeding periods (6 months), complementary food becomes critical for infant health. To identify the preference and food variety in homemade complementary food, and correlate it with family characteristics and anemia in infant, we conducted a cross-sectional studies. Participants were 51 pairs of infants (6-10 months old) and their mothers in Magelang regency, Central Java, Indonesia. Questionnaires on family characteristics and complimentary food were used. Infant Haemoglobin (Hb) levels m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“… 18 A study among 6–12 month-old children also showed that younger mothers tend to give less variety in homemade complementary food, heightening the risk of child malnutrition. 19 This result conforms to other research findings in Indonesia on stunting at birth in children, indicating the lowest risk for stunting among mothers 20–35 years old, 20 although in this study, this age range was 25–35 years.…”
Section: Discussionsupporting
confidence: 92%
“… 18 A study among 6–12 month-old children also showed that younger mothers tend to give less variety in homemade complementary food, heightening the risk of child malnutrition. 19 This result conforms to other research findings in Indonesia on stunting at birth in children, indicating the lowest risk for stunting among mothers 20–35 years old, 20 although in this study, this age range was 25–35 years.…”
Section: Discussionsupporting
confidence: 92%